Clinical features in a family with an R460H mutation in transforming growth factor β receptor 2 gene. Issue 12 (2nd August 2006) - Law, C; Bunyan, D; Castle, B; Day, L; Simpson, I; Westwood, G; Keeton, B
Abstract : Objectives: To describe the clinical findings and natural history in 22 carriers of an R460H mutation in the transforming growth factor β receptor 2 gene (TGFβR2) from a five-generation kindred ascertained by familial aortic dissection. Methods: 13 of the confirmed carriers were interviewed and examined, and information about the remaining carrier was obtained from medical records. Clinical information about deceased individuals was obtained, when possible, from postmortem reports, death certificates and medical records. Results: There have been eight sudden deaths; the cause of death was aortic dissection in all six cases in which a postmortem examination was performed. Three individuals had undergone aortic replacement surgery. Dissection had occurred throughout the aorta, and in one case in the absence of aortic root dilatation. Subarachnoid haemorrhage, due to a ruptured berry aneurysm, had occurred in two individuals. Four gene carriers and one deceased family member who were investigated had tortuous cerebral blood vessels. One had tortuous vertebral arteries, two had tortuous carotid arteries and one a tortuous abdominal aorta. Two individuals were found to have a brachiocephalic artery aneurysm and a subclavian artery aneurysm, respectively. Conclusions: Despite the predisposition to aortic dilatation and dissection, individuals did not frequently manifest the skeletal features of Marfan syndrome, with the exception of joint hypermobility. No one individual had ocular lens dislocation. Striae and herniae were common. There was some overlap with Ehlers–Danlos syndrome type 4, OMIM 130050, with soft translucent skin, which is easily bruised. Other features were arthralgia, migraine and a tendency to fatigue easily, varicose veins and prominent skin striae. This family provides further evidence that mutations in TGFβR2 cause a distinct syndrome that needs to be distinguished from Marfan syndrome to direct investigation and management of patients and shows the natural history, spectrum of clinical features and variable penetrance of this newly recognised condition.